Design and operation of power systems with large amounts of wind power, first results of IEA collaboration - Holttinen, Hannele (2013)
An international forum exchange of knowledge of power systems impacts of wind power has been formed under the IEA Implementing Agreement on Wind Energy. The task 'Design and Operation of Power Systems with Large Amounts of Wind Power Production' will analyse existing case studies from different power systems. There is a multitude of studies made and ongoing related to cost of wind integration. However, the results are not easy to compare. This paper summarises the results from 10 countries and outlines the sudies made at European Wind Energy Association and the European system operators UCTE and ETSO. A more in-depth review of the studies is needed to draw conclusions on the range of integration costs for wind power. State-of-the art review process will seek for reasons behind the wide range of results for costs of wind integration-definitions for wind penetration, reserves and costs; different power system and load characteristics and operational rules; underlying assumptions on variability of wind etc.